2002
DOI: 10.1152/ajpheart.00741.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac overexpression of A1-adenosine receptor protects intact mice against myocardial infarction

Abstract: Previous studies have shown that high-level (300-fold normal) cardiac overexpression of A1-adenosine receptors (A1-ARs) in transgenic (TG) mice protects isolated hearts against ischemiareperfusion injury. However, this high level of overexpression is associated with bradycardia and increased incidence of arrhythmia during ischemia in intact mice, which interfered with studies to determine whether this line of TG mice might also be protected against myocardial infarction (MI) in vivo. For these studies, we ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 26 publications
(34 reference statements)
3
50
0
Order By: Relevance
“…GLUT4 is an important transporter for the entry of glucose into myocardial cells, and NADH dehydrogenase is a mitochondrial enzyme involved in the first step of the electron transport chain. The role of these proteins in cellular ATP production supports the hypothesis that their overexpression could contribute to the preservation of ATP stores during ischemia (7) and possibly the overall tolerance to ischemia-reperfusion injury afforded by A 1 AR overexpression (12,13,25). Another previous finding in transgenic mice is the observation of altered adrenergic responsiveness of Ltype calcium channel current in myocytes isolated from transgenic hearts (unpublished results).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…GLUT4 is an important transporter for the entry of glucose into myocardial cells, and NADH dehydrogenase is a mitochondrial enzyme involved in the first step of the electron transport chain. The role of these proteins in cellular ATP production supports the hypothesis that their overexpression could contribute to the preservation of ATP stores during ischemia (7) and possibly the overall tolerance to ischemia-reperfusion injury afforded by A 1 AR overexpression (12,13,25). Another previous finding in transgenic mice is the observation of altered adrenergic responsiveness of Ltype calcium channel current in myocytes isolated from transgenic hearts (unpublished results).…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, hearts with overexpression of A 1 ARs show improved cardiac energetics during ischemia, compared with wild-type hearts (7). Finally, we have observed that transgenic animals overexpressing A 1 ARs have reduced infarct size in response to in vivo regional ischemia (25).…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Magnesium reduced infarct size also via enhancement of the action of adenosine in rabbits [625]. Over-expression of A1R protected mice against MI [626]. The use of intravenous adenosine after primary coronary stenting reduced the infarct size [627].…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…Although all four AR subtypes are expressed in the mammalian heart (11,12), the well-known protective effects of adenosine in this tissue are predominantly mediated by the adenosine A 1 receptor (A 1 AR) subtype, especially under conditions of ischemia and reperfusion injury (13)(14)(15)(16)(17). Unfortunately, the transition of A 1 AR agonists into the clinic has been severely hindered because of high doses causing on-target bradycardia, atrioventricular block, and hypotension (13,18). As a consequence, clinical trials of AR agonists have had limited success because of the suboptimal dose of agonist that can be used (19)(20)(21)(22).…”
mentioning
confidence: 99%